Pengaruh Financial Distress, Capital Intensity, Leverage, dan Cash Flow terhadap Konservatisme Akuntansi - Rosa Biuti Kartika; Martini Martini (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of financial distress, capital intensity, leverage, and cash flow on accounting conservatism. The research focuses on companies in the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The sample was selected using a purposive sampling technique based on predetermined criteria to ensure the relevance of the data analyzed, resulting in 71 companies meeting the requirements for this study. The analytical method employed is multiple linear regression analysis, utilizing the SPSS version 22.0 statistical tool.The results of this study indicate that financial distress, capital intensity, and leverage have a negative and significant effect on accounting conservatism. This suggests that companies experiencing financial difficulties, having high capital intensity, and high leverage ratios tend to exhibit lower levels of accounting conservatism in their financial reporting. This occurs because companies often avoid conservative financial statements to present better financial performance to investors and creditors. Conversely, cash flow shows a positive and significant effect, indicating that companies with strong cash flows face less financial pressure, leading to increased conservative financial reporting as management opts for greater transparency.